Maternal Weight Gain and its Relationship with Birth Weight of Baby at Term (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: Perinatal health is influenced by maternal weight gain. Increase in obesity in population and excess weight during pregnancy may be different complications including large for gestational age fetus. As a result cesarean delivery has increased in prevalence. Maternal weight gain during the 2nd and 3rd trimesters is an important determinant of fetal growthObjective: To determine the relationship between maternal weight gain and birth weight of baby at term.Methodology : A cross sectional study was carried among 50 pregnant women at term in the Department of Obstetrics and Gynaecology, Shaheed Suhrawardy Medical College and Hospital and Anwer Khan Modern Medical College Hospital during the period of January 2013 to July 2013. Data were collected in pre-designed data collection sheet.Results: This study found maximum (36%) were age group 21-25 years followed by 28% were ≤20 years, 24% were between 26-30 years, 8% were between 31-35 years and only 4% were of 36-40 years. The average age was 25 years. Among these 50 pregnant women, 2 cases (4%) had BMI < 18.5, 15 cases (30%) had a BMI 18.5-24.9, 19 cases (38%) had a BMI 25-29.9 and 14 cases (28%) had a BMI ≥30. The mean birth weight was 2.77±0.33. kg. Mean weight gain was 10.72±3.72 Kg.Conclusion: This study showed that reasonable maternal weight gain significantly increased birth weight of the baby at term.Bangladesh J Obstet Gynaecol, 2017; Vol. 32(2) : 79-83